Fintech Startups in Germany: Firm Failure, Funding Success, and Innovation Capacity - Lars Hornuf; Matthias Mattusch (CESifo GmbH, 2024)
Fintech startups have set out to revolutionize the financial world. However, little is known about how successful and innovative these firms actually are. This paper investigates firm failure, funding success, and innovation capacity using a hand-collected dataset of 892 German fintechs founded between 2000 and 2021. We find that founders with a business degree and entrepreneurial experience have a better chance of obtaining funding, while founder teams with science, technology, engineering, or mathematics backgrounds file more patents. Early third-party endorsements and foreign partnerships substantially increase firm survival. We also establish the following stylized facts: (1) fintechs focusing on business-to-business models and which position themselves as technical providers prove to be more effective; and (2) fintechs competing in segments traditionally reserved for banks are generally less successful and less innovative. These results have important implications for the early-stage success management of fintech firms and the investment decisions of venture capital funds and government startup programs.
Keywords: G24; M13; 330; Fintech industry; firm funding; firm failure; innovation capacity